Corrective Feedback in Learning Interaction: Integration of Surface Strategy Taxonomy - Yeasy Agustina Sari; Linda Septiyana; Suhono Suhono; Aria Septi Anggaira; Umar Al Faruq A. Hasyim (STAI Hubbulwathan Duri, 2021)
The article aimed to determine the types of errors found in classroom learning interactions at (Perguruan Tinggi Keagamaan Islam) PTKI Metro, to analyze the strategies used in correcting student errors in classroom learning interactions at PTKI Metro and to know the aspects of Surface Strategy Taxonomy which was found in classroom learning interaction errors at PTKI Metro. In analyzing the data, the researchers used the theory of Dalton-Puffer (2007) which was used to find out and describe the types of common student errors in the interaction of learning English in the classroom. Then, using the theory offered by Mendez at al (2010) which is applied to analyze the types of lecturer strategies in correcting student errors in learning. The researcher also analyzed the linguistic aspects of the taxonomy category in the student's errors using the theory of Dulay, Burth, and Krhashen (1982). The results show that the corrective feedback strategies used by lecturers at PTKI Metro City were Explicit Correction, Recast, Clarification Request, and Metalinguistic Feedback. And this study also classifies the types of errors based on the Aspects Surface Strategy Taxonomy on learning interactions in the classroom.